Eckol, a potential inhibitor of aryl hydrocarbon receptor, inhibits proliferation and induces apoptosis in breast cancer cells - Pelin Balcik-Ercin (Bangladesh Pharmacological Society, 2022)
The present study was designed to explore phlorotannin eckol protein targets and evaluate the anti-cancer effects of eckol against human breast cancer cells. ProTox-II server and protein-ligand docking analysis deter-mined the aryl hydrocarbon receptor (AhR) as a putative target of eckol. The AhR has been determined as a potential target for breast cancer treatment. The effect of eckol treatment on proliferation, apoptosis, and cell cycle activities was detected in MDA-MB-231 and SK-BR-3 breast cancer cell lines which were selected dependent on AhR expression profiles. Consistent with the AhR expression profile, MDA-MB-231 cells were more sensitive to eckol treatment compared to SK-BR-3 cells in proliferation, apoptosis and cell cycle results. Eckol treatment shows a significant antiproliferative and apoptotic response in breast cancer cells. Overall, these results indicated that the action of eckol may be related to the AhR gene regulation in different breast cancer cell lines.